EQUIVALENCE IN TRANSLATION. CHALLENGES AND SOLUTIONS (Ustozlar uchun, 2026)
Equivalence has long been considered one of the central concepts in translation studies. It refers to the degree of similarity between the source text and the target text in terms of meaning, style, and communicative effect. However, achieving equivalence remains one of the most challenging aspects of translation due to linguistic, cultural, and contextual differences between languages. This article explores the theoretical foundations of equivalence, identifies the main challenges translators face, and proposes practical solutions and strategies. While machine translation has advanced significantly, human translators continue to play a crucial role in ensuring cultural sensitivity, creativity, and contextual appropriateness.